FAKTORFAKTOR YANG MEMPENGARUHI PELAPORAN KEUANGAN MELALUI INTERNET (INTERNET FINANCIAL REPORTING) PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Mellisa Prasetya; Soni Agus Irwandi (STIE Perbanas Surabaya, 2012)
The internet development is increasing to disseminate financial information thats usuallycalled Internet Financial Reporting (IFR). The purpose of this study was to examine of factorsthat affect financial reporting of the manufacturing industry on the Indonesian StockExchange. IFR helps enterprises to disseminate financial information faster and to reducecost such as printing and mailing annual reports. This study used test of normality and multiplelinier regression analysis for developing the hypothesis framework. The surveys findingsshow that factor of firm size influence the internet financial reporting. Many enterprises presentonly product and service advertising. However, other factors such as profitability, liquidity,leverage, and listing age do not explain the company choice to use IFR.